Frontal free‐radical photopolymerization of thick samples: Applications to LED‐induced fiber‐reinforced polymers. Issue 8 (18th February 2019) - Carion, Pauline; Ibrahim, Ahmad; Allonas, Xavier; Croutxé‐Barghorn, Céline; L'Hostis, Gildas
ABSTRACT: Free‐radical photopolymerization is scarcely used for the manufacturing of fiber‐reinforced polymers. The main issue relies on the penetration depth of light which affects the conversion degree when photopolymerizing thick samples. Consequently, this could lead to inhomogeneous polymer properties. The ability of acylphosphine oxides to photobleach under near UV irradiation makes them of great interest for the curing of thick samples. Therefore, the influence of (2, 4, 6‐trimethylbenzoyl) phosphine oxide on the curing of composites under LED is investigated. Although that a frontal photopolymerization process can be evidenced, it was found that full photobleaching is hardly obtained at high concentration of photoinitiator. Six layers laminates made of unidirectional fiber glass and unsaturated polyester resin were prepared. The existence of an optimal range of concentration for which the conversion of the resin is the most homogeneous throughout its thickness was pointed out, a fact that is confirmed by dynamic mechanical analysis. Interestingly, this effect is reflected in the shrinkage of the resin as shown by direct measurements or deflection experiments. Mechanical analysis was undertaken whose results correlate well with the aforementioned study, demonstrating the occurrence of a balance between the concentration of photoinitiator and the mechanical properties of the samples. © 2019 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2019, 57, 898–906 Abstract : The effect of the penetration depth of light during the frontal free‐radical photopolymerization of LED‐cured fiber‐reinforced polymers is studied. The photobleaching of the photoinitator is shown to be incomplete, leading to inhomogeneities in properties. An optimal range of photoinitiator concentration is pointed out which allows the formation of high performance composites.